2017
DOI: 10.3233/cbm-170251
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of long noncoding RNA PVT1 predicts unfavorable prognosis in patients with clear cell renal cell carcinoma

Abstract: PVT1 may be an oncogene as well as may promote metastasis in ccRCC and could serve as a potential biomarker to predict the prognosis of ccRCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 66 publications
2
30
1
Order By: Relevance
“…One major finding of our study is that high PVT1 expression is tightly associated with several clinical parameters and a poor prognosis in SCCHN patients, which is consistent with reports in other solid tumors including non-small-cell lung cancer 10 , 12 , hepatocellular carcinoma 15 , clear renal cell carcinoma 35 , prostate cancer 17 , glioma 36 , 37 , gastric 23 and cervical cancer 38 , etc. We have to mention that our current clinical analysis is based on a relative small sample size, therefore, verification in a larger patient cohort will further strengthen the clinical significance of PVT1 in SCCHN patients.…”
Section: Discussionsupporting
confidence: 90%
“…One major finding of our study is that high PVT1 expression is tightly associated with several clinical parameters and a poor prognosis in SCCHN patients, which is consistent with reports in other solid tumors including non-small-cell lung cancer 10 , 12 , hepatocellular carcinoma 15 , clear renal cell carcinoma 35 , prostate cancer 17 , glioma 36 , 37 , gastric 23 and cervical cancer 38 , etc. We have to mention that our current clinical analysis is based on a relative small sample size, therefore, verification in a larger patient cohort will further strengthen the clinical significance of PVT1 in SCCHN patients.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with our findings, it has been reported that LINC01094 plays its pro-tumor role in the development of ccRCC by regulating the miR-224-5p/CHSY1 axis ( Jiang et al, 2020 ). Whilst, lncRNA PVT1 has been indicated to function as a tumor promoter that has a significant role in the metastasis in ccRCC ( Bao et al, 2017 ). Moreover, Jiang et al (2020) have reported that LINC01094 was activated by FOXM1 at the transcriptional level and their experimental indicated that LINC01094 acts as a sponge of miR-224-5p while CHSY1 was a miR-224-5p-targeted mRNA indicating the potential value of miR-224-5p/CHSY1 regulatory axis.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the advances of high-throughout technology, numerous lncRNAs have been detected and profiled and many of them participated in RCC progression. For example, lncRNA PVT1 was shown to be upregulated in ccRCC, which was associated with poor outcome [10] due to its promotion of cell proliferation and invasion by competitively binding with miR-200 family through regulating the expression of metastasis related genes [11]. Similarly, Xu et al identified that increased lncRNA PANDAR expression correlated with an advanced TNM stage and with lymph node involvement and distant metastasis in ccRCC and PANDAR downregulation induced cell cycle arrest and apoptosis in RCC cells [5].…”
Section: Introductionmentioning
confidence: 99%